2021
DOI: 10.3389/fpls.2021.640606
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Apple Calli With a Focus on the Key Genes for ALA-Induced Anthocyanin Accumulation

Abstract: The red color is an attractive trait of fruit and determines its market acceptance. 5-Aminolevulinic acid (ALA), an eco-friendly plant growth regulator, has played a universal role in plant secondary metabolism regulation, particularly in flavonoid biosynthesis. It has been widely reported that ALA can up-regulate expression levels of several structural genes related to flavonoid metabolism and anthocyanin accumulation. However, the molecular mechanisms behind ALA-induced expression of these genes are complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 99 publications
0
21
0
Order By: Relevance
“…It is regarded as a plant growth promoting hormone since many studies found that it could regulate the growth and development of higher plants. Instead of only focusing on the effects of 5-ALA on plant, more and more researchers began to use omics to explain its mechanism (Zheng et al, 2021). The role of 5-ALA in stimulating physiochemical processes in higher plants under stress, regulating plant growth and development in seed germination, vegetative growth and fruit coloring has been reviewed by (Wu et al, 2018.…”
Section: Biological Effects and Applications Of 5-aminolevulinic Acid...mentioning
confidence: 99%
“…It is regarded as a plant growth promoting hormone since many studies found that it could regulate the growth and development of higher plants. Instead of only focusing on the effects of 5-ALA on plant, more and more researchers began to use omics to explain its mechanism (Zheng et al, 2021). The role of 5-ALA in stimulating physiochemical processes in higher plants under stress, regulating plant growth and development in seed germination, vegetative growth and fruit coloring has been reviewed by (Wu et al, 2018.…”
Section: Biological Effects and Applications Of 5-aminolevulinic Acid...mentioning
confidence: 99%
“…Infection was carried out according to the method of Zheng [28]. The recombinant plasmids were inserted into A. tumefaciens GV3101 cells and then transformed in apple calli.…”
Section: Mdscl8 Mdhy5 and Mdmyb22 Cloning And Transformation Into App...mentioning
confidence: 99%
“…5-Aminolevulinic acid (ALA), a natural and environmentally friendly multifunctional plant growth regulator [22,23], has been extensively verified for its efficacy in improving plant resistance to abiotic stress [24,25], leaf photosynthetic performance [26], and anthocyanin accumulation [27,28]. Importantly, ALA has been proven to significantly promote the accumulation of flavonol in guard cells of Arabidopsis thaliana [29], 'Fuji' apple fruits [30], and apple calli [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-Seq, an efficacious technique for probation of plant functional genomics, has been applied in a wide range of studies of fruit trees. Based on this technology, large amounts of sequence information and expression data can be obtained [18,28]. In the present study, the molecular mechanism by which lignin forms in hardened pear fruit was probed using RNA-Seq.…”
Section: Introductionmentioning
confidence: 99%